Spatiotemporal regulation of MELK during mitosis - Majumdar, Sreemita; Liu, Song-Tao (Frontiers in Cell and Developmental Biology, 2024)
Maternal Embryonic Leucine Zipper Kinase (MELK) has been studied intensively in recent years due to its overexpression in multiple cancers. However, the cell biology of MELK remains less characterized despite its well-documented association with mitosis. Here we report a distinctive pattern of human MELK that translocates from the cytoplasm to cell cortex within 3 minutes of anaphase onset. The cortex association lasts about 30 minutes till telophase. The spatiotemporal specific localization of MELK depends on the interaction between its Threonine-Proline (TP) rich domain and kinase associated 1 (KA1) domain, which is regulated by CDK1 kinase and PP4 protein phosphatase. KA1 domains are known to regulate kinase activities through various intramolecular interactions. Our results revealed a new role for KA1 domain to control subcellular localization of a protein kinase.